2008
DOI: 10.1513/pats.200705-058vs
|View full text |Cite
|
Sign up to set email alerts
|

Force Fluctuation induced Relengthening of Acetylcholine-contracted Airway Smooth Muscle

Abstract: Superimposition of force fluctuations on contracted tracheal smooth muscle (TSM) has been used to simulate normal breathing. Breathing has been shown to reverse lung resistance of individuals without asthma and animals given methacholine to contract their airways; computed tomography scans also demonstrated bronchial dilation after a deep inhalation in normal volunteers. This reversal of airway resistance and bronchial constriction are absent (or much diminished) in individuals with asthma. Many studies have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(77 reference statements)
2
7
0
Order By: Relevance
“…The effect of increasing tone on the strain and decline of force caused by simulated breathing maneuvers has never been systematically investigated. However, previous studies have shown that ASM preshortened with high concentrations of ACh relengthens when subjected to force oscillations simulating breathing maneuvers (7,16,17,20,25). This phenomenon was dubbed force fluctuation-induced relengthening (7,17,20).…”
mentioning
confidence: 99%
“…The effect of increasing tone on the strain and decline of force caused by simulated breathing maneuvers has never been systematically investigated. However, previous studies have shown that ASM preshortened with high concentrations of ACh relengthens when subjected to force oscillations simulating breathing maneuvers (7,16,17,20,25). This phenomenon was dubbed force fluctuation-induced relengthening (7,17,20).…”
mentioning
confidence: 99%
“…Since the force produced by ASM in response to a given contractile stimulus is attenuated following an acute stretch (40), the bronchodilating and bronchoprotective effect of DI seen in vivo may be due to a regulated intrinsic property of ASM. It has also been recognized that fluctuating strains applied to ASM cause a decline in force (10,12,13,20,31) as well as a relengthening of contracted ASM (21,24). In contrast, breathing at low lung volume was shown to increase airway responsiveness (8) and cessation of tidal breathing during breath holding caused a decrease in tracheal and central bronchi diameter (25).…”
Section: Discussionmentioning
confidence: 99%
“…The stress excursions, and the attendant strain, experienced by ASM in vivo are important to consider because they alter ASM mechanics considerably(reviewed in [27]). Simulation of breathing maneuvers on ex vivo preparations of ASM decrease ASM force when the muscle is held in isometric condition [28] and cause re-lengthening when ASM is subjected to an isotonic or auxotonic load [29,30]. This suggests that the changes of lung volume occurring in vivo due to breathing maneuvers may be protective against excessive airway responsiveness because it decreases ASM contractility.…”
Section: Transpulmonary Pressure Swings That Stress and Strainmentioning
confidence: 99%